การศึกษาคุณลักษณะอันพึงประสงค์ด้านความซื่อสัตย์สำหรับนักเรียนชั้นประถมศึกษาปีที่ 4 - ถูวะสี, ศิริรัตน์ (วารสารศรีล้านช้างปริทรรศน์, 2018)
การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อศึกษาระดับคุณลักษณะอันพึงประสงค์ด้านความซื่อสัตย์ สำหรับนักเรียนชั้นประถมศึกษาปีที่ 4 โรงเรียนบ้านกุดสะเทียนใหม่ศรีทอง ในการศึกษาครั้งนี้มีกลุ่มตัวอย่าง ได้แก่ นักเรียนชั้นประถมศึกษาปีที่ 4 โรงเรียนบ้านกุดสะเทียนใหม่ศรีทองในปีการศึกษา 2561 จำนวน 25 คน เครื่องมือที่ใช้ในการการเก็บรวบรวมข้อมูลเป็นแบบสอบถามแบบมาตราส่วนประมาณค่า 5 ระดับ โดยนาข้อมูลที่ได้มาวิเคราะห์ด้วยวิธีการทางสถิติ ได้แก่ ร้อยละ ความถี่ ค่าเฉลี่ย (x̄) และค่าเบี่ยงเบนมาตรฐาน (S.D.)          ผลการวิจัยพบว่า นักเรียนชั้นประถมศึกษาปีที่ 4 โรงเรียนบ้านกุดสะเทียนใหม่ศรีทอง มีระดับคุณลักษณะอันพึงประสงค์ ด้านความซื่อสัตย์ โดยรวมอยู่ในระดับมาก (x̄ = 3.98) เมื่อพิจารณาเป็นรายด้าน พบว่า นักเรียนมีคุณลักษณะอันพึงประสงค์ด้านซื่อสัตย์สุจริต ในรายข้อที่มีค่าเฉลี่ยสูงสูด คือ ไม่เอาสิ่งของ ของคนอื่นมาเป็นของตน ตามมาด้วยนักเรียนสามารถแยกแยะได้ว่าสิ่งใดถูกสิ่งใดผิด ไม่โกหกต่อเพื่อนและครู ปฏิบัติตนโดยคำนึงถึงความถูกต้อง ละอาย และเกรงกลัวต่อการกระทำผิด และปฏิบัติตามคำมั่นสัญญา             The aims of this research were: 1) to studied the level of students’ desirable characters on honesty aspect of Prathomsuksa 4 students at Ban Kut Sathian Mai Si Thong School School. The sample in this study was 25 of Prathomsuksa 4 students, who study in academic year 2018, of Bankudsatienmaisritong School, Sriboonruang district, Nong Bua Lamphu province. The instrument used to collect the data was the 5 rating scale questionnaire. The statistical techniques used were frequency, percentage, mean (x̄) and standard deviation (S.D.)             The results of the research showed that studied the level of students’ desirable characters on honesty aspect of Prathomsuksa 4 students at Bankudsatienmaisritong School, over all were at high level. When considering in each aspect When considering in each aspect found that the aspect with the highest mean is Students don't bring other people's belongings, followed by Students can identify what is right and what is wrong, Students do not lie to friends and teachers, Students conduct themselves with due regard for their rightfulness, ashamed and afraid of wrongdoing, and Students comply with their promises.